The Digital Story Tool For English Language Classroom in Higher Education - Said, Ratna (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This paper describes the design of educational digital story tool for English language classroom in higher education to support and overcome students' learning difficulties. The method in this research is a literature study which aims to reveal and explain theories that can answer the research objectives.The method in this research is a literature study which aims to examine a research problem. Lecturers can choose a digital story tool pratform that is able to create an interactive and innovative class atmosphere with the application such as storybird, StoryboardThat, and Klynt.